2005
DOI: 10.1111/j.1365-2222.2005.02237.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability of total serum immunoglobulin E levels from birth to the age of 10 years. A prospective evaluation in a large birth cohort (German Multicenter Allergy Study)

Abstract: In childhood, tIgE levels underlie remarkable variation over time even in the absence of atopy. For cross-sectional population-based genetic and epidemiologic studies, tIgE values of children <5 years should be interpreted with caution since these values correlate poorly with tIgE levels later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 21 publications
7
35
0
Order By: Relevance
“…In line with our study findings, other studies have described higher values of total serum IgE for male children [27] and adults [6,28] as compared to females. Kulig et al [1] found significantly higher values in boys, also in a group of nonatopic children.…”
Section: Discussionsupporting
confidence: 83%
“…In line with our study findings, other studies have described higher values of total serum IgE for male children [27] and adults [6,28] as compared to females. Kulig et al [1] found significantly higher values in boys, also in a group of nonatopic children.…”
Section: Discussionsupporting
confidence: 83%
“…Elevated levels of total-serum IgE are not a good predictor of atopy since levels vary widely with age (2197). Elevated total IgE levels are more likely to correlate with the presence of atopic dermatitis than with allergic rhinitis.…”
Section: Diagnosismentioning
confidence: 99%
“…However, categorized data were significantly associated with the presentation of allergic diseases in newborns. This could be explained by evidence that suggested that total serum IgE levels and nasal eosinophil counts could be influenced by additional factors, including age and genetic factors [34]. …”
Section: Discussionmentioning
confidence: 99%